Analysis of the use of air-admittance valves in Brazilian sanitary sewer systems - Fernandes, Vera Maria Cartana (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This article presents an analysis of the ventilation conditions inside sanitary sewer systems of residential buildings when the secondary ventilation, usually accomplished by means of branches and columns, is replaced by air-admittance valves. Three tests were performed in prototypes of sanitary sewer systems associated to Brazilian building typologies, in which the pressure in different points of the system was measured, and the performance of seal traps was assessed. The prototypes were tested with several sanitary appliance flow arrangements, as well as with different types of ventilation systems, always starting with the sanitary sewer system which had only primary ventilation.The aim of this work is to provide designers of building sanitary sewer systems with guidelines for safely conceiving and dimensioning the ventilation subsystem, as well as replacing secondary ventilation pipes by air-admittance valves. .